2020
DOI: 10.1101/2020.04.22.050385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent evolution of p38/MAPK activation in hormone resistant prostate cancer mediates pro-survival, immune evasive, and metastatic phenotypes

Abstract: SummaryAdaptation of cancer cells to targeted therapy follows ecological paradigms observed in natural populations that encounter resource depletion and changing environments, including activation of pro-survival mechanisms, migration to new locations, and escape of predation. We identified the p38 MAPK pathway as a common molecular driver of these three responses during the adaptation to hormone therapy resistance in prostate cancer. The p38 pathway is activated in therapy-resistant cells and mechanistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 90 publications
3
21
0
Order By: Relevance
“…Oncoviruses such as EBV and HPV have been associated with increased PD-L1 levels (Farrukh et al 2021). Likewise, EMT is also correlated with upregulation of immune checkpoints (Ware et al 2020; Chakraborty et al 2021). These relationships prompted us to investigate whether oncovirus-positive samples were enriched in PD-L1 activity and/or expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncoviruses such as EBV and HPV have been associated with increased PD-L1 levels (Farrukh et al 2021). Likewise, EMT is also correlated with upregulation of immune checkpoints (Ware et al 2020; Chakraborty et al 2021). These relationships prompted us to investigate whether oncovirus-positive samples were enriched in PD-L1 activity and/or expression.…”
Section: Resultsmentioning
confidence: 99%
“…Given the relationship between PD-L1 and EMT (Ware et al 2020; Chakraborty et al 2021), we also analyzed the correlations between PD-L1 activity and EMT scores across our entire cohort of datasets. We observed that the PD-L1 activity score was more likely to be positively correlated with a Mes score (22 out of 28 datasets in Fig 4C ) than with an Epi signature (15 out of 28 datasets in Fig 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Our modeling framework predicts that the emergence of enzalutamide resistance must be accompanied by a change in the metabolic profile of tumor cells including an increase in glucose uptake. A recent study has shown that the activities of signaling pathways that regulate cell metabolism, including the p38 pathway, are indeed altered by enzalutamide treatment in prostate cancer cells [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our modeling framework predicts that the emergence of enzalutamide resistance must be accompanied by a change in the metabolic profile of tumor cells including an increase in glucose uptake. A recent study has shown that the activities of signaling pathways that regulate cell metabolism, including the p38 pathway, are indeed altered by enzalutamide treatment in prostate cancer cells (57). Multiple studies have shown a tight coupling between cell-type switching and change in the metabolic state of cells, especially in the context of epithelial-mesenchymal plasticity.…”
Section: Discussionmentioning
confidence: 99%